2014
DOI: 10.1097/wnr.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α upregulation in microglia following hypoxia protects against ischemia-induced cerebral infarction

Abstract: Activated microglia were considered to be the toxic inflammatory mediators that induce neuron degeneration after brain ischemia. Hypoxia can enhance the expression of hypoxia-inducible factor-1α (HIF-1α) in microglia and cause microglial activation. However, intermittent hypoxia has been reported recently to be capable of protecting the body from myocardial ischemia. We established a high-altitude environment as the hypoxic condition in this study. The hypoxic condition displayed a neuroprotective effect after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Semi‐quantitative single‐cell PCR would be required to confirm this assumption. It is also conceivable that Kv channel activation is modulated by post‐transcriptional and post‐translational regulation (Huang et al, ) or by other mechanisms such as interaction with enzymes (Combs, Shin, Xu, Ramu, & Lu, ) or peptides (Feng et al, ; Xie et al, ). Based on our findings, Kv1.5 and in particular Kv3.1 are less likely to contribute to the observed upregulation of outward currents in plaque‐associated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Semi‐quantitative single‐cell PCR would be required to confirm this assumption. It is also conceivable that Kv channel activation is modulated by post‐transcriptional and post‐translational regulation (Huang et al, ) or by other mechanisms such as interaction with enzymes (Combs, Shin, Xu, Ramu, & Lu, ) or peptides (Feng et al, ; Xie et al, ). Based on our findings, Kv1.5 and in particular Kv3.1 are less likely to contribute to the observed upregulation of outward currents in plaque‐associated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in vessel reactivity followed by reperfusion could induce hypoxic stress on the endothelium, resulting in BBBD (43). Molecular analysis following pFUS+MB-induced vasospasm (31) has not been investigated adequately, but the increases in protein expression or mRNA reported here in HSP70, TNFα, IL1α, IL1β, VEGF, and EPO would be consistent with decreased perfusion and reperfusion within the targeted parenchyma (9,12,19,(44)(45)(46)(47). The rapid increase in TNFα and other proinflammatory factors indicates an acute involvement of NVU elements in response to hypoxia or injury (14,48).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of HP are mediated via the transcription factor hypoxia-inducible factor-1 (HIF-1) (Bergeron et al, 2000;Sharp et al, 2001) and various target genes, which initiate angiogenesis, erythropoiesis, glucose store mobilization and therefore, cell survival. Recent studies have shown the protective effects of hypoxia to be mediated by HIF-1␣, where knockout mice were not protected by HP (Sheldon et al, 2014), and pharmacological blockade of HIF-1 was able to prevent hypoxia-induced microglial activation (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%